2006
DOI: 10.1007/s00359-006-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

Modification of leech behavior following foraging for artificial blood

Abstract: In this study we examined whether the foraging for artificial blood affected the behavioral responsiveness of leeches to electrical stimulation of the body wall. After foraging for artificial blood, electrical stimulation of the posterior end of the leech significantly increased the percentage of stimulation trials that elicited locomotory activity--swimming and crawling--compared to the behaviors elicited when leeches did not forage or foraged for normal saline. On the other hand, shortening always dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Hungry H. verbana use both visual (Dickinson and Lent, 1984) and mechanical (Young et al, 1981) cues from water waves to determine whether prey is present and which direction to move. Chemical cues also promote swimming during foraging behavior (Brodfuehrer et al, 2006). Once contact is made with a potential host, both thermal and chemical cues govern the decision to feed.…”
Section: Neuronal Mechanisms and Decision To Initiate And Terminate Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Hungry H. verbana use both visual (Dickinson and Lent, 1984) and mechanical (Young et al, 1981) cues from water waves to determine whether prey is present and which direction to move. Chemical cues also promote swimming during foraging behavior (Brodfuehrer et al, 2006). Once contact is made with a potential host, both thermal and chemical cues govern the decision to feed.…”
Section: Neuronal Mechanisms and Decision To Initiate And Terminate Fmentioning
confidence: 99%
“…This diversity in serotonin action can in some cases be explained by whether serotonin is applied to the brain or within specific regions within the segmental ganglia (Crisp and Mesce, 2003; Calviño and Szczupak, 2008). Additionally, we do not know which sensory neurons activate these serotonergic neurons, although it is likely that the lip chemoreceptors (Elliott, 1986, 1987) are a major source because the suppression of other behaviors is observed during the exploration of a potential food item even before the leech begins to feed (Gaudry and Kristan, 2009) and when full strength artificial blood is presented at ambient temperature to the lip of head-intact isolated nerve cord preparations (Brodfuehrer et al, 2006). Furthermore, chemosensory stimulation is known to activate some of the serotonergic neurons (Groome et al, 1995; Zhang et al, 2000).…”
Section: Short-term Inhibition Of Competing Behaviorsmentioning
confidence: 99%
“…The presence of food can bias the choice of behavioral response: the likelihood of large tail flips (which move the animal further from the food) decreases when food is present, as does the activity of medial giant interneurons (which receive tactile and visual inputs) that drive the tail flip response. Medicinal leeches ignore mechanosensory stimulation that would normally elicit locomotion behaviors in the presence of artificial blood [30]. Pinching the tail of a marine slug ( Aplyisa californica ) can elicit either feeding or locomotory behavior, and serotonergic neurons sensitive to food modulate the choice between these two behaviors [31].…”
Section: Environmental Context Modulates Behavioral Choicementioning
confidence: 99%
“…The medicinal leech has a clear behavioral hierarchy, with feeding taking precedence over all other behaviors [43]. Following up the earlier study by Brodfuehrer et al, (2006) [30] showing decreased responsiveness to touch in the presence of artificial blood, Gaudry and Kristan [44••] found that when a leech is actively engaged in feeding on blood, serotonin presynaptically inhibits the connections between mechanosensory neurons and interneurons that mediate other behaviors such as swimming, crawling, shortening and bending (Figure 2A). This inhibition, which makes the leech able to maintain feeding and be unresponsive to even intense mechanosensory sensation, was observed behaviorally in sanguivorous (bloodsucking) species, but not carnivorous species [45].…”
Section: Current Internal or Behavioral State Modulates Sensorimotor mentioning
confidence: 99%
“…The identification of multifunctional projection interneurons raises the question as to how the same activity pattern in these interneurons can encode the initiation process of multiple behaviors. It is generally thought that the behavior elicited depends on the integration of multiple factors such as sensory cues, hormone or neuromodulator levels, and behavorial state (Brodfuehrer et al 2006;Hedwig 2000;Libersat and Pflueger 2004;Matsuura et al 2002;Watson and Ritzman 1994).…”
Section: Introductionmentioning
confidence: 99%